Geodata and landscape: from the cloud to lectures - María Luisa de Lázaro y Torres; Sara Izquierdo Álvarez; María Jesús González González (Boletín de la Asociación de Geógrafos Españoles, 2016)
Geography is a science that easily integrates the latest technological developments, both in the field of research and in teaching and professional practice. Innovative visualisation tools available on the cloud facilitate new research results, and also promote learning and a better understanding of the landscape and its typologies. This is demonstrated by employing the technique of storytelling, geographical itineraries and agrarian landscapes.